Systematic And Un-Systematic Factors Influencing Profitability In The Energy Sector Of Pakistan - Sikandar Hayat , Bilal Idress, Dr. Jawad Karamat, Naseer Muhammad, Muhammad Subhan, Dr.Arshad Iqbal (Migration Letters, 2024)
The purpose of the study is to investigate the Micro and Macro Dynamics that affect the energy sector during the study period of 2018-2023 by using the most reliable models of the panel data analysis. The factors of financial leverage and age are positive while liquidity, risk, GDP, growth, and size significantly affect financial Performance. Moreover, tangibility, market share, interest rate, and inflation rate have insignificant impacts on return on assets (ROA).On the other hand, analyze the influence of factors that determine financial performance on return on equity (ROE).Financial leverage, growth, risk, tangibility, liquidity, GDP, and INF are positive and significantly related, while risk, tangibility, and INF have an insignificant influence on ROE. Thus. ROE is significantly and positively influenced by financial leverage, growth, liquidity, and GDP. The factors of size, age, market share, and interest rate are not statistically significantly related to return on equity (ROE). The energy should be focused on internal factors that will enhance the efficiency of the industry by providing valuable services. It also recommended that systematic factors must be considered while making major decisions.